Dnevnici Božene Loborec. - SABOLOVIĆ-KRAJINA, DIJANA (Prodravski zbornik, 2023)
This work aims to provide insight into some previously unknown or lesser-known aspects of the life and work of the writer Božena Loborec (Koprivnica, June 2, 1926 -- Koprivnica, January 3, 2003) from the angle of her diary entries. She wrote her diaries intimately, for herself and far from the view of others. Still, she decided to leave them to us today and to generations to come with a message: "In 50 years or later, someone will surely find these writings interesting because they will be a document of my present time." The diaries are an interesting source of information for at least two reasons: they reflect the private life of the leading intellectual and writer from Koprivnica in the last thirty years of the 20 century, and at the same time, they are a kind of chronicle of life and the history of Koprivnica in the context of social, political, and cultural movements in Croatian and Yugoslav society, as well as in the world during that period. The multi-layered diaries of Božena Loborec can also be interpreted as a unique micrology of Koprivnica, encompassing several hundred individuals, many of whom are no longer alive, as well as recognizable locations and sites of Koprivnica, many of which no longer exist. Božena Loborec wrote her diary in her distinctive sharp and clear, playful and witty, analytical-rational, and ironically satirical style, sparing neither herself nor others. Two mottos outline the intentions of the diarist Božena Loborec: "Pametan pamti, mudar zapisuje" (The intelligent remember, the wise write) and "Verba volant, scripta manent" (Words fly away, writings remain).